Construindo proximidades e distanciamentos: etnografia Tupi Guarani da Terra Indígena Piaçagüera/SP - Mainardi, Camila (2010)
This research was carried out through fieldwork in the Piaçagüera Indigenous Land, located on the southern coast of São Paulo, between 2007 and 2009. It proposes an analysis of the Tupi Guarani relations construction with other indigenous groups, especially with Guarani Mbya, non-Indians, and also the relations between themselves. In a context of territorial conflict and the formation of a new village in which they discussed ways to rescue the culture, I realized that people can operate distances and approaches to what they consider being Guarani, Tupi and indigenous people, based on a speech that deals with the mixture. The Tupi Guarani people say that they are mixed because of the marriages that occurred between the Guarani and the Tupi as the basis of their ethnicity. They also speak about the mixture with other Indians and whit nonindigenous people - like white and black people. It thus becomes clear that they establish a kind of gradation between being "more Indian" and "less Indian" that is linked to characteristics typically considered Guarani, for example, the mobility and the territoriality. Through the relationships that the Tupi Guarani people establish among themselves and with others, it is possible to understand how the knowledge and the knowing the language, prayers, traditions and the Tupi and Guarani ethnic identities are constructed and constantly updated.